International consensus to define outcomes for trials of chemoradiotherapy for anal cancer (CORMAC-2): defining the outcomes from the CORMAC core outcome set - Robert Samuel; Stephen R. Knight; Richard Adams; Prajnan Das; Jennifer Dorth; David Finch; Marianne G. Guren; Maria A. Hawkins; Susan Moug; Lakshmi Rajdev; David Sebag-Montefiore; Andrew G. Renehan; et al. (EClinicalMedicine)
Summary: Variation in outcomes definitions and reporting limit the utility of clinical trial results. The Core Outcome Research Measures in Anal Cancer (CORMAC) project developed a core outcome set (COS) for chemoradiotherapy trials for anal squamous cell carcinoma (ASCC) through an international healthcare professional and patient consensus process. The CORMAC-COS comprises 19 outcomes across 4 domains (disease activity, survival, toxicity, life impact). In CORMAC-2 we have established standardised definitions for the 11 disease activity and survival outcomes in the CORMAC COS. Definitions were agreed through a 3 step process, initially identifying existing definitions through systematic review (registered with PROSPERO, CRD42016036540), using these to populate a two-round Delphi questionnaire completed by 51 experts from 13 countries, and finally ratification through an online consensus meeting. Standardising the definitions for these core outcomes facilitates real world utilisation of the CORMAC-COS, thereby increasing the quality of data available for clinical decision-making and ultimately enhancing patient care.